Cooperative Extension professionals' knowledge and attitudes toward the opioid epidemic: Implications for capacity development and outreach - Washburn, Lisa T.; Franck, Karen L.; Upendram, Sreedhar; Yenerall, Jackie N. (Frontiers in Psychiatry, 2022)
Introduction. Worsening of the opioid epidemic amplifies calls for involvement of the nationwide Cooperative Extension System (Extension) in addressing this crisis. Understanding knowledge and attitudes of Extension professionals who directly interact with communities is critical given identified needs for increased capacity and substantial federal investments supporting Extension’s opioid response. This study explored opioid knowledge and attitudes among Extension professionals in one state to identify attitudes and perceptions that may influence community-level efforts. Method. An online survey including 25 Likert scale questions about attitudes and beliefs related to substance use was administered. Questions were categorized into five concept areas: treatment and community support, legal and punitive approaches, substance use as an illness, external causes of substance use, and personal causes of substance use. Descriptive statistics and response frequencies for all variables were calculated. Geographic differences between the state’s three Extension regions were calculated using one-way ANOVAs. Results. Survey responses (n=236) indicated respondents recognized complexity of the opioid crisis and had favorable attitudes toward treatment and community support approaches. Support for legal and punitive approaches was mixed, as were attitudes toward external and personal causes of substance use. Most indicated needing better resources and more knowledge to engage in work locally. Conclusion. Increased capacity is needed in Extension to adequately support families and communities dealing with substance use disorder. Findings suggest areas of focus and provide insight for others seeking to develop capacity in opioid response by engaging Extension professionals or other community outreach workers in substance use prevention efforts.